2013
DOI: 10.1371/journal.pone.0082907
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Association of COX-2 (Cyclooxygenase-2) Immunoexpression with Prognosis in Human Osteosarcoma: A Meta-Analysis

Abstract: BackgroundNumerous studies examining the relationship between Cyclooxygenase-2 (COX-2) immunoexpression and clinical outcome in osteosarcoma patients have yielded inconclusive results. MethodsWe accordingly conducted a meta-analysis of 9 studies (442 patients) that evaluated the correlation between COX-2 immunoexpression and clinical prognosis (death). Pooled odds ratios (OR) and risk ratios (RR) with 95% confidence intervals (95% CI) were calculated using the random-effects or fixed-effects model. ResultsMeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Peng et al37 found that COX-2 765G>C polymorphism was associated with colorectal cancer risk. Another study by Wang et al38 found that COX-2 overexpression was associated with poor prognosis and cancer progression. COX-2 765G>C is a functional polymorphism located at 765 bp upstream (2,765 bp) from the transcription starting site.…”
Section: Discussionmentioning
confidence: 97%
“…Peng et al37 found that COX-2 765G>C polymorphism was associated with colorectal cancer risk. Another study by Wang et al38 found that COX-2 overexpression was associated with poor prognosis and cancer progression. COX-2 765G>C is a functional polymorphism located at 765 bp upstream (2,765 bp) from the transcription starting site.…”
Section: Discussionmentioning
confidence: 97%
“…COX-2 expression has been found to be associated with an increased risk of tumor recurrence, advanced cancer stage and/ or poor overall survival in a large number of cancers such as ovarian cancer [28,29], osteosarcoma [30,31], pancreatic cancer [32], gastric cancer [33][34][35], classical Hodgkin's lymphoma [36], oral squamous cell cancer [37], melanoma [38], non-small cell lung cancer [39] but not lung adenocarcinoma [40], clear cell renal carcinoma [41], cervical cancer [42] and esophageal adenocarcinoma [43]. The specific expression of COX-2 in breast and colon cancers is detailed later in this article.…”
Section: Cox-2 Expression In Cancermentioning
confidence: 99%
“…COX-2 was also found overexpressed frequently in osteosarcoma, which promoted malignant potential of neoplasms [ 20 , 21 ] and was associated with poor prognosis for patients with osteosarcoma [ 22 , 23 ]. Celecoxib, a selective COX-2 inhibitor, can induce osteosarcoma cell apoptosis via inhibiting COX-2 [ 24 , 25 ], and has been applied for the clinical trials to treat osteosarcoma and Ewing sarcoma [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%